New species of Glyphohesione and Pseudexogone (Annelida, Pilargidae) from the Gulf of Thailand - Plathong, Jintana; Plathong, Sakanan; Dean, Harlan K. (Zootaxa, 2024)
Two new species of Pilargidae, Glyphohesione pattaniensis sp. nov. and Pseudexogone losinensis sp. nov. are described from the southern Gulf of Thailand, Pattani Province. Glyphohesione pattaniensis sp. nov. is clearly distinguished from all other known species in the genus by having lateral antennae on the middle of the prostomium; lacking ventral cirri at chaetiger 2; first notopodial spines beginning at chaetiger 6; and having small epidermal papillae. Pseudexogone losinensis sp. nov. belongs to a group of species in the genus with eyespots present and differs from all other described species by the shape of the furcate chaetae with a strongly curved large tine and a tine with an open tip. An updated key to the species of Glyphohesione and Pseudexogone and a world map of both genera are also provided.
Annelidabase